A Mini Review on Technique of Milk Thermization - Angela Nitia Nefasa; Marcelinus Christwardana; Zakaria Hussein Abdurrahman; Fatkur Rohman; Agus Afif (Journal of Bioresources and Environmental Sciences, 2023)
Thermization is a preheating procedure in which milk is heated at low temperatures for a brief time prior to further processing. It is often used in the dairy processing industry to make a variety of products, including pasteurized milk, milk powder, and cheese. Eliminating psychrophilic bacteria, avoiding milk spoiling, and halting the changes generated by lipase and protease enzymes are the objectives of this method. Despite the fact that thermization enhances the shelf life of milk, it may also result in sensory changes and the germination of B. cereus spores. The goal of the thermization method is to prepare milk for the upcoming processing stage, and the temperature and length of the process might vary. Thermization does not affect the flavor of milk or dairy products such as yogurt, but it may enhance the quality of cheese by decreasing the occurrence of stale and rancid flavors. The process may be carried out in a plate heat exchanger or as a pre-pasteurization treatment for raw milk to protect milk quality during lengthy storage in insulated silos.